2020
DOI: 10.4103/ijo.ijo_1280_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of three Descemet membrane endothelial keratoplasty injectors on endothelial damage of grafts

Abstract: Purpose: Various injectors are commercially available for Descemet membrane endothelial keratoplasty (DMEK) but not all injectors have been studied for endothelial damage of grafts. The aim of the study was to compare endothelial damage in pre-stripped DMEK tissue from three clinically used injector devices: the modified Jones tube, the STAAR intraocular (IOL) injector, and the Geuder glass cannula in a laboratory setting. Methods: Twenty-four human donor corneas were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study concluded that the Geuder cannula may offer a significant reduction in tissue damage. 79 DMEK Rapid device DMEK Rapid, a relatively new Geuder system, has an aperture diameter of 1.6 mm, a posterior loading orifice of 4.29 mm and a smooth opening edge profile. In a laboratory investigation, DMEK Rapid compared with conventional flask showed 9.15% and 10.35% ECL respectively.…”
Section: Intra Ocular Lens Cartridgementioning
confidence: 99%
“…The study concluded that the Geuder cannula may offer a significant reduction in tissue damage. 79 DMEK Rapid device DMEK Rapid, a relatively new Geuder system, has an aperture diameter of 1.6 mm, a posterior loading orifice of 4.29 mm and a smooth opening edge profile. In a laboratory investigation, DMEK Rapid compared with conventional flask showed 9.15% and 10.35% ECL respectively.…”
Section: Intra Ocular Lens Cartridgementioning
confidence: 99%